Prognostic value of different serum biomarkers for left ventricular remodelling after ST-elevation myocardial infarction treated with primary percutaneous coronary intervention. Issue 15 (9th May 2012) - Urbano-Moral, Jose Angel; Lopez-Haldon, Jose Eduardo; Fernandez, Monica; Mancha, Fernando; Sanchez, Angel; Rodriguez-Puras, Maria Jose; Villa, Manuel; Lopez-Pardo, Francisco; Diaz de la Llera, Luis; Valle, Juan Ignacio; Martinez, Angel
Abstract : Background: Mortality derived from ST-elevation myocardial infarction (STEMI) has decreased due to primary percutaneous coronary intervention (PCI). Paradoxically, the incidence of heart failure secondary to left ventricular remodelling (LVR) is on the rise due to the survival derived from reperfusion strategies. The aim of this study was to assess the prognostic value for LVR of biomarkers involved in several pathophysiological mechanisms activated during STEMI treated with primary PCI. Methods: 112 patients with STEMI undergoing primary PCI were evaluated. LVR was defined as a ≥20% increase in the left ventricular end-diastolic volume at 6-month follow-up assessed using echocardiogram as compared with that at discharge. Blood samples were obtained for glucose, N-terminal pro-brain natriuretic peptide, troponin T (TnT), matrix metalloproteinase 9, procollagen type-I N-terminal propeptide and high-sensitivity C reactive protein (hs-CRP). Results: 24 patients (21%) developed LVR. Higher levels of maximum TnT, and matrix metalloproteinase 9 and hs-CRP at discharge, were detected as independent risk factors for LVR (OR 1.310, p=0.03; OR 1001, p=0.04; OR 1.040, p=0.04, respectively). Both TnT and hs-CRP showed significant ability to distinguish patients who developed LVR from those who did not, being the values that yielded the greatest sensitivity and specificity as follows: TnT 7.0 μg/l (73%, 84%), hs-CRP 30 mg/l (59%, 85%). Conclusions: Myocardial necrosis, as measured by released TnT, and inflammation state evident due to circulating levels of CRP are factors that may play a major role in the development of LVR following STEMI treated with primary PCI.